The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2166/wp.2018.093
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in primary production in the Seto Inland Sea, Japan, after implementing regulations to control the pollutant loads

Abstract: A total pollutant load control system (TPLCS) was implemented in the Seto Inland Sea in 1979 to reduce the water pollution and the frequency of red tides. We estimated primary production from 1981 to 2010 to determine the effects of reducing the nutrient loadings from the surrounding land. While primary production has decreased overall in the Seto Inland Sea in response to the TPLCS and the associated reductions in the total nitrogen (T-N) and phosphorus (T-P) loads from land since 1981, the reductions were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that nutrient loadings in Japan have decreased over recent decades (e.g., Yamamoto-Kawai et al 2015;Kamohara et al 2018;Nakai et al 2018), with variable effects on summer pHinsitu in coastal waters. TN was monitored for a shorter period than pHinsitu (1995 to 2009).…”
Section: Regional Differences In Phinsitu Trendsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported that nutrient loadings in Japan have decreased over recent decades (e.g., Yamamoto-Kawai et al 2015;Kamohara et al 2018;Nakai et al 2018), with variable effects on summer pHinsitu in coastal waters. TN was monitored for a shorter period than pHinsitu (1995 to 2009).…”
Section: Regional Differences In Phinsitu Trendsmentioning
confidence: 98%
“…8). The pH trends in coastal areas of western Kyushu, where the anthropogenic nutrient loadings are relatively low, therefore reflect the decreases in nutrient discharges, resulting in variations between regions (e.g., Nakai et al 2018;Yamamoto and Hanazato 2015;Tsuchiya et al, 2018). Several cities in this area have introduced advanced sewage treatment to prevent eutrophication in coastal waters (Nakai et al 2018;Yamamoto and Hanazato 2015).…”
Section: Regional Differences In Phinsitu Trendsmentioning
confidence: 99%
“…type, magnitude, frequency and timing), connectivity with adjacent systems and differing water quality parameters (Carstensen et al, 2011;Duarte et al, 2015). In successful cases, the improvement appeared in nutrients, Chl.a, dissolved oxygen concentrations and seagrass cover after implementation of the programme (Greening et al, 2014;Riemann et al, 2016;Nakai et al, 2018;Nishijima et al, 2018), whereas little improvement or even worsening were unfortunately reported too (Williams et al, 2010;Riemann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, stable and appropriate primary production by phytoplankton, as well as by seagrasses and benthic microalgae, is essential to sustain the healthy functioning of ecosystems and the sustainable supply of fishery resources (Takai et al, 2002;Hoshika et al, 2006;Nakai et al, 2018). Phytoplankton growth will directly respond to nutrient supply, whereas the growth and distribution of benthic macro-and microalgae will be determined by both nutrient supply and light availability; the latter will also be affected by nutrient supply through phytoplankton growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation